A new species of Mecomera Audinet-Serville earwig (Dermaptera: Spongiphoridae) from the Brazilian Atlantic Rainforest - Heleodoro, Raphael Aquino (Zootaxa, 2021)
A new earwig species, Mecomera ze sp. nov. (Spongiphoridae: Sparattinae: Sparattini) from the Brazilian Atlantic Rainforest is described based on males and females from Piracicaba, São Paulo, Brazil. Mecomera ze sp. nov. has a pygidium shape similar to that of M. chacoensis (Borelli), and can be differentiated by the flattened projections of M. ze sp. nov., with emarginations between each projection, whilst in M. chacoensis the pygidium has cylindrical projections, with a single emargination between apical projections. Mecomera ze sp. nov. is also similar to M. reichardti in that both have cerci as long as the abdomen. However, M. reichardti has an inconspicuous basal projection and a more acute conspicuous projection at middle, whilst M. ze sp. nov. has a more conspicuous basal projection and less conspicuous middle projection. Comparisons are made with the male genitalia of all species.